Combination of Antiestrogens and Omega-3 Fatty Acids for Breast Cancer Prevention. (3rd August 2015) - Manni, Andrea; El-Bayoumy, Karam; Skibinski, Christine G.; Thompson, Henry J.; Santucci-Pereira, Julia; Bidinotto, Lucas Tadeu; Russo, Jose
Abstract : The molecular and biological heterogeneity of human breast cancer emphasizes the importance of a multitargeted approach for effective chemoprevention. Targeting the estrogen receptor pathway alone with the antiestrogens, Tamoxifen and Raloxifene reduces the incidence of estrogen receptor positive tumors but is ineffective against the development of hormone independent cancers. Our preclinical data indicate that the administration of omega-3 fatty acids potentiates the antitumor effects of Tamoxifen by inhibiting multiple proliferative and antiapoptotic pathways, several of which interact with estrogen receptor signaling. The complementarity in the mechanism of antitumor action of Tamoxifen and omega-3 fatty acids is well supported by our signaling, genomic, and proteomic studies. Furthermore, administration of omega-3 fatty acids allows the use of lower and, hence, likely less toxic doses of Tamoxifen. If these findings are supported in the clinical setting, the combination of omega-3 fatty acids and anteistrogens may emerge as a promising, effective, and safe chemopreventive strategy to be tested in a large multi-institutional trial using breast cancer incidence as the primary endpoint.